PENGARUH PENGGUNAAN MEDIA BERBASIS HIPERTEXT PADA MATERI POKOK STRUKTUR ATOM DAN TABEL PERIODIK TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 3 MAKASSAR - Ahmad, Fandi (STKIP Pembangunan Indonesia Makassar, 2014)
This research is a quasi experiment that aims to determine the effect the use of hypertext-based as media on atomic structure and periodic table to the study results of the students Class X of SMAN 3 Makassar with